If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + (1 + -2x) = 11 Remove parenthesis around (1 + -2x) 7x + 1 + -2x = 11 Reorder the terms: 1 + 7x + -2x = 11 Combine like terms: 7x + -2x = 5x 1 + 5x = 11 Solving 1 + 5x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5x = 11 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = 11 + -1 5x = 11 + -1 Combine like terms: 11 + -1 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 3x^2-2x=-19x-10 | | a/5=3.05 | | 4h+10=7p-13 | | (3x+15)(x-1)=0 | | 25x+5(-10-5x)=18 | | 0=-16T^2+158t+102 | | Cos(3x)=-1/2 | | 15x-50=3x | | Y=5x^2+20x-9 | | (2x-2)(3x+15)=0 | | 3/5m | | 7x-4(24-5x)=12 | | 7x-4(24-5x)=24 | | p(h-1)+w(-h-1)+(h-1)= | | w/4.7=.93 | | 2(17-10y)+6y=6 | | 5p+9=-91 | | (-6-2x)(-4x+8)=0 | | 2/3x-1/61/2 | | k(q+r)-b(q+r)-q-r= | | 5n+6n=77 | | 0.5t/125 | | 105/41= | | 12y-8=56 | | (3x-3)(x+2)=0 | | 7x(n^2+2)+(n^2+2)(b^2+3)= | | 3x-4(x-8)=28 | | (-2-x)(3x-9)=0 | | (m-2)(m-3)+(m-2)(m+4)= | | (2y-8)-y=28 | | 5y(c^2+1)+(c^2+1)(r^2+1)= | | 3/10n-4/5 |